Maskulinitetsperspektiv på kriminologiens kjerneområder: Kontroll, ofre og kriminalitet - Nina Irene Jon (Nordisk Tidsskrift for Kriminalvidenskab)
The aim of this article is to render visible and problematise conceptions and norms for performing masculinity within criminology. Approaching crime and crime control from a gendered perspective is highly relevant: Crime and punishment are historically among the most gendered fields in society, predominantly inhabited by men. While the relation between crime and masculinity was actually addressed by some of the subcultural theorists in the 1950s (see e.g., Cohen 1955, Bloch and Niederhoffer 1958, Kvaraceus and Miller 1959, Cloward & Ohlin 1960), criminology as such has by and large remained a gender-blind discipline. The article focuses on the impact a gender perspective can have on the core areas of criminology: control, victimization and crime.